Trends in shaken baby syndrome diagnosis codes among young children hospitalized for abuse - Aislinn Conrad; Brandon Butcher; Resmiye Oral; Megan Ronnenberg; Corinne Peek-Asa (BMC, 2021)
Abstract Objective To investigate national trends of SBS diagnosis codes and how trends varied among patient and hospital characteristics. Methods We examined possible SBS, confirmed SBS, and non-SBS abuse diagnosis codes among children age three and younger who were hospitalized for abuse between 1998 and 2014 using a secondary analysis of the National Inpatient Sample, the largest US all-payer inpatient care database (N = 66,854). A baseline category logit model was used based on a quasi-likelihood approach (QIC) with an independent working correlation structure. Results The rate (per 100,000 census population of children age 3 and younger) of confirmed and possible SBS diagnosis codes was 5.4 (± 0.3) between 1998 and 2014, whereas the rate of non-SBS abuse was 19.6 (± 1.0). The rate of confirmed SBS diagnosis codes increased from 3.8 (± 0.3) in 1998 to 5.1 (± 0.9) in 2005, and decreased to 1.3 (± 0.2) in 2014. Possible SBS diagnosis codes were 0.6 (± 0.2) in 1998, increasing to 2.4 (± 0.4) in 2014. Confirmed SBS diagnosis codes have declined since 2002, while possible SBS diagnosis codes have increased. All abuse types were more frequent among infants, males, children from low-income homes, and urban teaching hospitals. Conclusions We investigated seventeen-year trends of SBS diagnosis codes among young children hospitalized for abuse. The discrepancy between trends in possible and confirmed SBS diagnosis codes suggests differences in norms for utilizing SBS diagnosis codes, which has implications for which hospital admissions are coded as AHT. Future research should investigate processes for using SBS diagnosis codes and whether all codes associated with abusive head injuries in young children are classified as AHT. Our findings also highlight the relativity defining and applying SBS diagnosis codes to children admitted to the hospital for shaking injuries. Medical professionals find utility in using SBS diagnosis codes, though may be more apt to apply codes related to possible SBS diagnosis codes in children presenting with abusive head injuries. Clarifying norms for SBS diagnosis codes and refining definitions for AHT diagnosis will ensure that young children presenting with, and coded for, abusive head injuries are included in overall counts of AHT based on secondary data of diagnosis codes. This baseline data, an essential component of child abuse surveillance, will enable ongoing efforts to track, prevent, and reduce child abuse.